Design and Control of Active Power Filters towards the Decarbonisation of Smart Grid Networks - Khadem, Shafiuzzaman Khan; Basu, M.; Komurcugil, Hasan (Elsevier, 2025)
Design and Control of Active Power Filters Towards the Decarbonisation of Smart Grid Networks offers an in-depth exploration of the essential role active power filters play in advancing modern energy systems. As the world transitions toward decarbonized power networks, this resource provides innovative approaches to enhance grid stability and improve power quality. With a focus on the shift from centralized high-voltage setups to decentralized, low-voltage smart grids, the book emphasizes how active power filters can address the challenges posed by fluctuating renewable energy sources and distributed generation. Beyond its technical focus, the book also delves into the practical strategies for implementing active power filters in real-world scenarios. It examines their impact on energy efficiency, reliability, and the overall resilience of decarbonized power systems. Readers will find valuable insights into optimizing filter design while navigating the complexities of integrating renewable energy technologies. Whether for researchers, engineers, or decision-makers, this book serves as a comprehensive guide for shaping the energy systems of tomorrow. © 2026 Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Energy efficiency; Natural resources; Power control; Renewable energy; Smart power grids; Active power Filter; Centralised; Decarbonisation; Design and control; Energy systems; Grid stability; Innovative approaches; Power; Power networks; Smart grid networks; Decarbonization